2009
DOI: 10.1111/j.1600-0501.2009.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year evaluation of the influence of keratinized mucosa on peri‐implant soft‐tissue health and stability around implants supporting full‐arch mandibular fixed prostheses

Abstract: Background The question of the importance of keratinized mucosa around dental implants for the prevention of peri-implant disease could not be answered in the relevant literature so far. Objective To investigate the influence of peri-implant keratinized mucosa on long-term peri-implant soft-tissue health and stability over a period of 5 years. Material and methods A total of 386 mandibular dental implants were placed in 73 completely edentulous patients, and subsequently restored with fixed full-arch prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
252
1
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(279 citation statements)
references
References 26 publications
14
252
1
12
Order By: Relevance
“…The consensus of opinions expressed by the authors participating in this debate was in general, supportive of the clinical practice of providing a keratinized gingival band around implant restorations where possible and practical. Another recent study reported a 5-year observation provided further data to support that keratinized gingival band of > 2 mm promotes better gingival health around dental implant/restorations (Schrott, Jimenez et al 2009). In a systemic review, Cairo and others concluded that in some clinical situations soft tissue augmentation is warranted (Cairo, Pagliaro et al 2008).…”
Section: The Keratinized Gingival Zonementioning
confidence: 99%
“…The consensus of opinions expressed by the authors participating in this debate was in general, supportive of the clinical practice of providing a keratinized gingival band around implant restorations where possible and practical. Another recent study reported a 5-year observation provided further data to support that keratinized gingival band of > 2 mm promotes better gingival health around dental implant/restorations (Schrott, Jimenez et al 2009). In a systemic review, Cairo and others concluded that in some clinical situations soft tissue augmentation is warranted (Cairo, Pagliaro et al 2008).…”
Section: The Keratinized Gingival Zonementioning
confidence: 99%
“…Schrott et al 30 observed that in patients with good hygiene records the presence of at least 2 mm of keratinized mucosa was significant to minimize bleeding and plaque accumulation on the lingual surface and soft tissue recession on the buccal surface of functioning dental implants. Therefore, the authors suggested that, in sites with insufficient keratinized mucosa, special attention should be driven in the maintenance of lingual surfaces and that a higher soft tissue recession should be expected on the buccal surface of dental implants.…”
Section: Keratinized Tissuementioning
confidence: 99%
“…Delaying implant placement (10) or performing soft tissue grafts and the placement simultaneously is recommended. It is currently believed that an adequate amount of soft tissue helps prevent marginal recession, hide the margins of the restoration and disguise the shadow in the implant platform (11,12) (Figs. 1, 2).…”
Section: A Intrinsic Factorsmentioning
confidence: 99%
“…Se recomienda o diferir la colocación del implante 10 o realizar injertos de tejido blando simultáneamente a su colocación. Actualmente se considera que una cantidad adecuada de tejido blando es útil en la prevención de la recesión marginal, ocultar los márgenes de restauración, y camuflar de la sombra de la plataforma del implante (11,12) (Figs. 1, 2).…”
unclassified